A brief review on smart grid residential network schemes - Noshin Fatima; Qasuria, Tahseen Amin; Mohd Adib Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Presently the domestic zone is a fundamental part of the overall energy consumption curve. Traditional energy control grids are facing dreadful complications while handling domestic users due to the rapid growth in energy demand. However, traditional grids are mainly dependent on coal, petrol, and other expensive resources, although these resources are limited and also causing air pollution. Hence, to avoid them, alternative resources should be considered for energy production. Literature showed that renewable resources like wind, water, thermal, and solar are some of the replacements for green energy production. Their foremost advantage is that they are natural and free which will aid in the production of economic and environmental-friendly energy on a large scale. However, the residential-side consumers should also utilize the electricity responsibly via the reduction in peak hour loads, by shifting loads to off-peak hours. This will be possible through using different optimal consumption schemes for demand-side management. In this article, home energy management system schemes are discussed to reduce electricity bills for domestic consumers by modifying the peak to average ratio. The suggested schemes can be used in the future, where automatic machines will be able to communicate and make intelligent decisions with the grid. The comparative study presents a summary concerning their methods, load and cost minimization, scheduling, pricing, and coverage range. As a result, customers can select the scheme according to their requirements or can combine two or more to achieve a different kind of benefits to utilizing energy both qualitatively and quantitatively.